Thirteen years daily and annual mean land surface temperature dataset over the Third pole - Youhua Ran; Xin Li; Kun Yang; Xianhong Meng; Shaoying Wang (PANGAEA, 2017)
The Qinghai-Tibet plateau (QTP), called "the Third Pole" of the earth, is the water tower of Asia that not only feeds tens of millions of people, but also maintains fragile ecosystems in arid region of northwestern China. Temporal-spatially complete representations of land surface temperature are required for many purposes in environmental science, especially in the Third pole where the traditional ground measurement is difficult and therefore the data is sparse. The thirteen years cloud-free datasets of daily mean land surface temperature (LST) and mean annual land surface temperature (MAST) during 2004 to 2016 are derived from the quartic daily MODIS (the Moderate Resolution Imaging Spectroradiometer) Terra/Aqua LST products with a resolution of 1 km using a pragmatic data processing algorithm. The comparison between radiance-based LST measurement and the estimated LST shows good agreement in the daily and inter-annual variability, with a correlation of 0.95 and 0.99 and bias of -1.73°C (±3.38°C) and -2.07°C (±1.05°C) for daily-mean-LST and MAST, respectively. The systematic error is mainly source from the defined of daily mean LST, which is represented by the arithmetic average of the daytime and nighttime LSTs. The random error is mainly source from the uncertainty of the original MODIS LST values, especially for the daytime LST products. Trend validation using air temperatures from 94 weather stations indicate that the warming trends derived from time series MAST data is comparable with that derived from CMA data. The dataset is potential useful for various studies, including climatology, hydrology, meteorology, ecology, agriculture, public health, and environmental monitoring in the Third pole and around regions.